PENEGAKAN HUKUM TINDAK PIDANA PERJUDIAN ONLINE DI KOTA PEKANBARU - Teddy Guntara; Mukhlis R; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Technological development is indeed positive effect on the development, but the development of technology also cause negative effects to the birth of the crime is the crime of gambling using the internet, or better known as online gambling. Through observation and distribution of a questionnaire conducted by the author, there are as many as 31 people who are doing this online gambling. But after the authors came none Pekanbaru Police handling the case of online gambling. The authors intend to examine the causes of the lack of online gambling cases handled by the Police Pekanbaru. The purpose of this thesis, namely; First, law enforcement against criminal acts of online gambling in the city of Pekanbaru, Second, barriers encountered in the enforcement of criminal law online gambling in the city of Pekanbaru, Third, efforts are being made to overcome barriers to the enforcement of criminal law online gambling in the city of Pekanbaru.From the results of research and discussion, it can be concluded that the First, law enforcement against criminal acts online gambling is done by preventive (prevention) ie, close all access to online gambling, appealed through advertising, forming community policing, and conduct raids Internet cafes. Second, obstacles to the enforcement of criminal law online gambling in Pekanbaru is the constraint of law enforcement / human resources, facilities and infrastructure constraints, the difficulty of obtaining evidence and arrest offenders, lack of public awareness, and legislation constraints. Efforts to overcome the barriers of law enforcement crime of gambling online is to conduct special training for police, complementary facilities and infrastructure, to form a special team to spy on places that are often used in accessing online gambling, provide legal counseling to the community and revise legislation.Keywords: Law Enforcement-Crime-Gambling-Online.